Who can work from home? The roles of job tasks and HRM practices - Kawaguchi, Daiji; Motegi, Hiroyuki (Journal of the Japanese and international economies, 2021)
•Examine the determinants of remote work using a unique Japanese survey dataset.•Remote work were prevalent among those engaged in non-routine tasks.•Remote work were prevalent among workers subject to HRM practices.•The expansion of remote work opportunities during COVID-19 was inequality enhancing.•Policy implications are discussed. This paper examines the characteristics of remote work using a unique Japanese survey dataset that provides information on engagement in remote work together with the specific job tasks and human resource management (HRM) characteristics workers face. We show that the opportunity to work remotely was more likely to be available to those engaged in non-routine tasks as well as to workers subject to HRM practices presupposing that worker performance is measurable. The implications of these findings for income transfer policies and management practices in light of the COVID-19 pandemic are also discussed.